Designing of Interdigitated Coordination Polymer for Fluorogenic Sensing of Pd(II) in Water with Reversible Nonphase Mechanochromism. Issue 31 (12th September 2022) - Dutta, Basudeb; Debsharma, Kingshuk; Dey, Sunanda; Naaz, Sanobar; Sinha, Chittaranjan; Mir, Mohammad Hedayetullah
Abstract: In the present study, a novel interdigitated coordination polymer (CP) [Zn(cit)(4‐nvp)] n (1 ) is synthesized using citraconic acid (H2 cit) and 4‐(1‐naphthylvinyl)pyridine (4‐nvp) mixed ligands. The efficient dipolar interactions between CP and polar solvents cause the observed redshift in emission spectra and rationalize the positive solvatochromism effect with increased Stokes shift (Δδ) from 5643 to 8547 cm −1 on going from less‐polar to more‐polar solvents. Supramolecular assembly of CP acts as a selective optical sensor toward Pd(II) even in the presence of other relevant contending metal ions in water. Inspired from the solution‐phase sensor activity, the CP is further employed for an on‐site and ecologically green contact mode detection of Pd(II) from water upon readily fabricating cost‐effective and portable thin film via simply drop‐casting aqueous suspension of material (1 mm ) on filter paper. Interestingly, the compound exhibits the rare mechanochromic behavior upon external pressure. Hence, the synthesized CP reveals sensing activity in diverse way; in one hand, it demonstrates solvatochromism and, in other hand, it unveils mechanochromism accompanied by the detection of Pd(II) in aqueous medium. Abstract : Here a rare example of interdigitated coordination polymer (CP), [Zn(cit)(4‐nvp)] n (H2 cit: citraconic acid and 4‐nvp: trans ‐4‐(1‐naphthylvinyl)pyridine) is highlighted, which exhibits solvatochromism as well as mechanochromism accompanied by the detection of Pd(II) sensing in ecologically green aqueous medium.